Differential cardiac remodeling in preload versus afterload - Toischer, Karl; Rokita, Adam G.; Unsöld, Bernhard; Zhu, Wuqiang; Kararigas, Georgios; Sossalla, Samuel; Reuter, Sean P.; Becker, Alexander; Teucher, Nils; Seidler, Tim; Grebe, Cornelia; Preuß, Lena; et al. (Circulation, 2010)
Background— Hemodynamic load regulates myocardial function and gene expression. We tested the hypothesis that afterload and preload, despite similar average load, result in different phenotypes. - - Methods and Results— Afterload and preload were compared in mice with transverse aortic constriction (TAC) and aortocaval shunt (shunt). Compared with sham mice, 6 hours after surgery, systolic wall stress (afterload) was increased in TAC mice (+40%; P<0.05), diastolic wall stress (preload) was increased in shunt (+277%; P<0.05) and TAC mice (+74%; P<0.05), and mean total wall stress was similarly increased in TAC (69%) and shunt mice (67%) (P=NS, TAC versus shunt; each P<0.05 versus sham). At 1 week, left ventricular weight/tibia length was significantly increased by 22% in TAC and 29% in shunt mice (P=NS, TAC versus shunt). After 24 hours and 1 week, calcium/calmodulin-dependent protein kinase II signaling was increased in TAC. This resulted in altered calcium cycling, including increased L-type calcium current, calcium transients, fractional sarcoplasmic reticulum calcium release, and calcium spark frequency. In shunt mice, Akt phosphorylation was increased. TAC was associated with inflammation, fibrosis, and cardiomyocyte apoptosis. The latter was significantly reduced in calcium/calmodulin-dependent protein kinase IIδ-knockout TAC mice. A total of 157 mRNAs and 13 microRNAs were differentially regulated in TAC versus shunt mice. After 8 weeks, fractional shortening was lower and mortality was higher in TAC versus shunt mice. - - Conclusions— Afterload results in maladaptive fibrotic hypertrophy with calcium/calmodulin-dependent protein kinase II-dependent altered calcium cycling and apoptosis. Preload is associated with Akt activation without fibrosis, little apoptosis, better function, and lower mortality. This indicates that different loads result in distinct phenotype differences that may require specific pharmacological interventions.